Kinerja Bank Syariah Pada Masa Pandemi Covid-19 Menggunakan Metode RGEC - Aa Ahmad Fauji (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This research was conducted to determine the performance of Islamic banks during the Covid-19 pandemic. This research method is descriptive with a quantitative approach. The data were obtained from the financial reports and Good Corporate Governance reports of 5 Islamic commercial banks that were sampled. The results showed that the performance of Islamic banks during the Covid-19 pandemic was seen from the Risk Profile with the NPF ratio the bank's performance was in good condition, while based on the FDR ratio the bank's performance was in quite good condition, on the Good Corporate Governance factor the bank's performance received a good predicate. The Earnings factor with the ROA ratio indicates that the bank's performance is in fairly good condition, based on the ROE ratio it indicates the bank's performance is in poor condition, while the assessment with the NOM ratio indicates the bank's performance is in very poor condition. Assessment using CAR shows that the performance of all Islamic banks is in the very good category